Conducting Redox Polymer Based Anode Materials for High Power Electrical Energy Storage. (20th June 2016) - Yang, Li; Huang, Xiao; Gogoll, Adolf; Strømme, Maria; Sjödin, Martin
Graphical abstract: Abstract: In this report we present the synthesis and characterization of two conducting redox polymers (CRPs) with polythiophene backbone and diethyl terephthalate pendant groups for the use as anode materials in secondary batteries. The materials show excellent rate capability allowing 30 μm layers to be fully converted within seconds without the use of conductive additives. The high rate capability is traced to the open morphology of the materials that allows for fast ion transport, and to the mediation of electrons through the conducting polymer (CP) backbone. The requirements for the latter are i) that the redox chemistry of the pendant groups and the CP backbone overlaps and ii) that the CP conductivity is not compromised by the presence of the pendant groups. In the CRPs presented herein both these requirements are met and this is thus the first report on successful combination of the redox chemistry of organic redox molecules with the n-doping of conducting polymers.